Motivational factors affecting employee Motivation in vietnamese equitized companies - Dao, Mai Anh (2020)
This study is designed to quantify the impact of motivational factors on employee motivation in Vietnamese equitized companies. To do that, the researcher establishes a determinant of research on the model in which employee motivation is influenced by relationship with colleagues, relationship with the leader, learning and developing opportunities, the meaningtulness of the work, employee recognition. The main data was collected from the survey with 100 employees working for Vietnamese equitized companies such as VNPT, Vietcombank, Agribank. Multiple linear regressions confirm that two factors significantly influence and positively motivate employees. Moreover, relationship with leader and learning and developing opportunities have the greatest impact on employee motivation. Based on the findings, a number of recommendations are made accordingly.